2009
DOI: 10.1073/pnas.0810928106
|View full text |Cite
|
Sign up to set email alerts
|

Segregating the core computational faculty of human language from working memory

Abstract: In contrast to simple structures in animal vocal behavior, hierarchical structures such as center-embedded sentences manifest the core computational faculty of human language. Previous artificial grammar learning studies found that the left pars opercularis (LPO) subserves the processing of hierarchical structures. However, it is not clear whether this area is activated by the structural complexity per se or by the increased memory load entailed in processing hierarchical structures. To dissociate the effect o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

39
301
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(347 citation statements)
references
References 44 publications
39
301
3
4
Order By: Relevance
“…Friederici and colleagues (2006) argue that their FMRI findings (p. 2458) ''show that the processing of these two sequence types [generated by a ''finite state" and a ''phrase structure" grammar, respectively] is supported by different areas in the human brain" and that their results (p. 2460) ''indicate a functional differentiation between two cytoarchitectonically and phylogenetically different brain areas in the left frontal cortex ["frontal operculum" and ''BA 44"]". Similar reasoning is found in Friederici, Bahlmann et al (2006), Friederici, Fiebach, Schlesewsky, Bornkessel, and von Cramon (2006), Bahlmann et al (2008), and Makuuchi et al (2009) 1 . In the context of these FMRI findings and suggestions, we raise the question whether Broca's region (or subregions) is specifically related to syntactic movement operations or the processing of hierarchically nested non-adjacent dependencies?…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…Friederici and colleagues (2006) argue that their FMRI findings (p. 2458) ''show that the processing of these two sequence types [generated by a ''finite state" and a ''phrase structure" grammar, respectively] is supported by different areas in the human brain" and that their results (p. 2460) ''indicate a functional differentiation between two cytoarchitectonically and phylogenetically different brain areas in the left frontal cortex ["frontal operculum" and ''BA 44"]". Similar reasoning is found in Friederici, Bahlmann et al (2006), Friederici, Fiebach, Schlesewsky, Bornkessel, and von Cramon (2006), Bahlmann et al (2008), and Makuuchi et al (2009) 1 . In the context of these FMRI findings and suggestions, we raise the question whether Broca's region (or subregions) is specifically related to syntactic movement operations or the processing of hierarchically nested non-adjacent dependencies?…”
Section: Discussionsupporting
confidence: 84%
“…In fact, dynamic functional Table 2 Overlap between the activated clusters in the listed studies and the clusters that we found activated in this region for the NG vs. G contrast. Columns 1-3: The [x, y, z] coordinates and the function labeling are taken from the studies: Makuuchi et al (2009), Bahlmann et al (2008, Friederici, Bahlmann et al (2006), Friederici, Fiebach et al (2006), Santi and Grodzinsky (2007a), Ben-Shachar et al (2003, 2004. Santi and Grodzinsky (2007b) reported the coordinates [À50 32 6] and [À50 33 8], but since this is a fixed-effects study we did not further analyze this here.…”
Section: Dynamic Functional Modularity and The Role Of The Left Infermentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, like the LPFC, occipital areas may support selection and manipulation of linguistic representations in working memory (47,48). Alternatively, the left occipital cortex might combine linguistic units into structured wholes (49) or support recursive structure building during sentence processing (12,33,50). Furthermore, just as there are distinct functions with the prefrontal cortex, so there may be distinct parts of the occipital cortex that support different high-level cognitive or linguistic functions.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of human language is that elementary linguistic units (words and morphemes) combine into higher-level structures, such as phrases and sentences. It has been suggested that language regions, such as Broca's area, have evolved to be uniquely suited for such combinatorial processing (12,33,34). Finding that occipital areas in early blind individuals are capable of combinatorial language processing would suggest that such processing does not require intrinsic biological prop-erties of classic language regions.…”
mentioning
confidence: 99%